Thực trạng hoạt động tự học của sinh viên Trường Đại học Võ Trường Toản - Nguyễn, Thanh Sơn; Trần, Lương (Tạp chí Giáo dục, 2025)
In the context of a fundamental and comprehensive reform in higher education, self-study plays a pivotal role in shaping and enhancing students’ competencies and personal attributes, thus meeting the demands of continuous and lifelong learning. This study seeks to evaluate the current state of self-study practices among students at Võ Trường Toản University, based on a questionnaire survey administered to 39 educational administrators, 68 lecturers, and 229 students. The findings reveal that, on average, students engage in self-directed learning only medium level on the scale. The use of modern self-study methods and tools remains limited, while the assessment and evaluation of self-study activities lack diversity and timely feedback. These results serve as a foundation for the university to propose appropriate strategies to foster students’ self-study, thereby contributing to the enhancement of educational quality.